Experimental performance evaluation of LoRaWAN: A case study in Bangkok - Vatcharatiansakul, Nuttakit; Tuwanut, Panwit; Pornavalai, Chotipat (My University, 2017)
The Internet of Things (IoT) is a vision which real-world objects are part of the internet. Every object is uniquely identified, and accessible to the network. There are various types of communication protocol for connect the device to the Internet. One of them is a Low Power Wide Area Network (LPWAN) which is a novel technology use to implement IoT applications. There are many platforms of LPWAN such as NB-IoT, LoRaWAN. In this paper, the experimental performance evaluation of LoRaWAN over a real environment in Bangkok, Thailand is presented. From these experimental results, the communication ranges in both an outdoor and an indoor environment are limited. Hence, the IoT application with LoRaWAN technology can be reliable in limited of communication ranges.
Keywords: Experimental Evaluation; Internet of Things; LoRA; LoRaWAN; LPWAN